Case Study on Public Health Preparedness in Malaysia - Lessons Learnt from Mount Kinabalu Earthquake - Maria Suleiman; Hazlina binti Yahaya; Phee Kheng Cheah; Abraham Zefong Chin (ASEAN Journal of Disaster Health Management (AJDHM), 2025)
Introduction: The earthquake of magnitude 6.0 on Richter scale that struck Mount Kinabalu on 5th June 2015 at 7.15 am Malaysia time (GMT+8) had significant impacts, affecting not only the climbers and staff at the site but also communities across Sabah. Mountain earthquake rescue operations present significant challenges due to the rugged terrain, remote locations, and complex logistics involved. Earthquakes in mountainous regions often trigger landslides, avalanches, and rockfalls, which can obstruct roads and complicate access for rescue teams. Objective: This paper aims to delineate the challenges of disaster health management, focusing on search and rescue response, public health management of temporary evacuation centres, post-event psychosocial support, and business continuity, particularly in the context of earthquake management in Sabah, Malaysia. Methods: Secondary data in the form of meeting minutes and event reports from the archives of Sabah State Health Department, Ministry of Health Malaysia, spanning the period from 5th June 2015 to 16th July 2015 was collected. Thematic coding scheme based on objective was developed. The findings derived from the analysis of meeting minutes and event reports were presented using narrative summaries in the results section of the paper. Results: The Mount Kinabalu earthquake response highlighted key areas for improvement in disaster preparedness and response. Challenges included poor interagency collaboration and communication issues due to inadequate infrastructure. The absence of early warning mechanisms and risk maps hampered search and rescue efforts, with responders relying on local guides. Medical responses were hindered by weather conditions. Managing mental health post-disaster was complex, requiring extensive support. Public health issues arose in evacuation centres due to disrupted water supplies. Additionally, damage to healthcare facilities necessitated the use of alternative locations to ensure service continuity. Conclusions: In summary, the Mount Kinabalu earthquake response highlighted the importance of investing in specialized training, equipment, local responders, and infrastructure to enhance preparedness and response capabilities, ultimately reducing the impact of similar disasters on communities and ensuring a more effective and coordinated response. Ongoing evaluation and adaptation based on lessons learned will be instrumental in improving disaster resilience in the region.